Debt Capitalization: A New Perspective on Ricardian Equivalence - David Stadelmann; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Rational individuals know that present government debts transform into higher future taxes. The Ricardian equivalence implies that the burden of the debt is not shifted between generations because of compensating intergenerational transfers. While the assumptions for Ricardian equivalence to hold are quite demanding, we argue that there exists another equivalence mechanism which works also with non-altruistic individuals: Public debts capitalize into property values. Thus, communities with larger net debts exhibit, ceteris paribus, lower property prices. We provide empirical evidence for debt capitalization using unique data for the Swiss metropolitan area of Zurich.
Keywords: H74; R51; H00; 330; Capitalization; Public Debts; Ricardian Equivalence; Taxes; Local Public Goods